Meeting the Black Swan: Teacher educators’ use of ICT—pre, during and eventually post Covid19 - Smith, Kari; Ulvik, Marit; Curtis, Elizabeth; Guberman, Ainat; Lippeveld, Lut; Shapiro, Tali; Viswarajan, Sheeba (Nordic Journal of Comparative and International Education (NJCIE), 2021)
In the 2018 International Forum for Teacher Educator Development (InFo-TED) Summer Academy, we, seven teacher educators from Belgium, England, Israel, Norway, and Scotland, became interested in strengthening our ICT competence. At an international conference in June 2019, we presented our personal stories about how we used ICT in our teaching, and what we wanted to learn more about. In June 2020 we wrote a new narrative describing our experiences with ICT which was forced upon us in the spring of 2020. In this narrative, we reflected on how we think our practice will change post-Covid-19. In this paper, we discuss our new narratives in relation to those we wrote in 2019. The two sets of stories were formed into seven vignettes seeking an answer to: 1) How did teacher educators (we) experience the Covid-19 which forced the need for change in working only online, and 2) How do we foresee that the current pandemic will change our future practice? The vignettes show we have had a steep learning curve regarding the technicalities of using ICT, exploring on our own as we were working from home. Moreover, we believe we will not return to pre-Covid-19 ways of teaching as we realise that ICT has not been fully exploited. Yet, we still need to find ways to combine ICT with our pedagogical visions as teacher educators. There are differences, benefits and disadvantages, related to our respective contexts, disciplines and competence. However, we found more similarities than differences. The latter is used to feed into each other’s professional learning. We all had to learn how to manage technical issues, and now we need to find ways to incorporate ICT critically and reflectively to model good teaching in teacher education. Covid-19 was a Black Swan which forced us to change. Now it is time to position ourselves as teacher educators in a changed reality.